Exercise Right Ventricular‐Pulmonary Arterial Coupling and Functional Outcome in Patients Undergoing Surgery for Secondary Ischemic Mitral Regurgitation - Carlo Fino; Diego Bellavia; Michele D'Alonzo; Maurizio Merlo; Vito D. Bruno; Julien Magne; Massimo Caputo; Amedeo Terzi; Michele Senni; Samuele Bichi; Caterina Simon; Edoardo Sciatti; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The exercise assessment of the right ventricular‐pulmonary arterial (PA) coupling adds diagnostic and prognostic value in patients with heart failure. In patients with ischemic mitral regurgitation undergoing surgery, data on the exercise assessment of the right ventricular‐PA coupling are not available. Resting and exercise echocardiographic predictors of functional outcome in patients with ischemic mitral regurgitation were tested. Methods Six‐minute walking test and exercise echocarrdiogram performed at baseline, at 1 years, and at a median follow‐up of 6 years (interquartile range, 3.70; range, 4.5–8) on 50 patients (67±8 years; ejection fraction: 35±5%) undergoing valve replacement or repair. Linear mixed models were used to evaluate the predictive value of preoperative echocardiographic parameters on the longitudinal distribution of the 6‐minute walking test. Results Preoperative exercise tricuspid annular plane systolic excursion (TAPSE)/PA systolic pressure strongly correlated with the long‐term 6‐minute walking test (r=0.81, P<0.01). The receiver operating characteristic analysis found a preoperative exercise TAPSE/PA systolic pressure <0.34 predicted the lowest quartile of the 6‐minute walking test in the long term (sensitivity: 79%; specificity: 100%) as well as a composite outcome of heart failure and death from any cause (positive predictive value: 91.3%, negative predictive value: 100%). On multivariable analysis, TAPSE and TAPSE/PA systolic pressure were significantly associated with a better long‐term 6‐minute walking test. Conclusions A preoperative exercise TAPSE/PA systolic pressure <0.34 predicts a poor functional performance and a higher likelihood of clinical adverse events. In patients with ischemic mitral regurgitation the exercise right ventricular ‐PA coupling could improve risk stratification. Larger studies are needed.